(untitled) (Journal of Faculty of Education, 2022)
This paper describes a development of an algorithm for nonlinear optimization using sequential quadratic programming (SQP) method. The computation is performed through a number of steps. The improvement of the performance is achieved and compared to a version with line search. هدفت هذه الورقة لتوضيح خطوات تطور خوارزمية إستناداً على الطريقة التقريبة للمعادلات التربيعية (SQP)حيت تم إنشاء خوارزمية لحساب القيم التفريبية لدالة الهدف وفق قيود محددة. ثم تم تنفيذ هذا البرامج لحل نماذج مختلفة من المعادلات الخطية والغير خطية.